Gambaran Kegiatan Toolbox Meeting dan Faktor Penyebab Kecelakaan Kerja di PT Adhi Persada Beton Plant Sadang Purwakarta - Agustina, Agustina; Hastuti, Riska (Jurnal Persada Husada Indonesia, 2020)
Toolbox meeting is a briefing activity that is carried out every day before starting work on each work section. Toolbox meeting is a form of Occupational Health and Safety promotion run by the company to reduce the number of work accidents. This study uses a qualitative design with the research approach used is phenomenology. The purpose of the study was to analyze the implementation of toolbox meeting activities in relation to work accidents at PT Adhi Persada Beton Plant Sadang, Purwakarta. Collecting data by conducting in-depth interviews, observations, and document review on 6 (six) informants to determine the characteristics of the informants, work experience, type of work, work shifts, and the incidence of work accidents. The results of the study indicate that the implementation of toolbox meeting activities as a refresh activity for workers, so that work behavior will change to safe behavior. Work experience has a role in work, because workers who have previous competence and expertise will have an impact on reducing the incidence of work accidents. The type of work is adjusted to the workers and their previous expertise or experience, which is expected to minimize the incidence of work accidents. Shift work at night has an impact on workers because the condition of the work area is minimally lit which makes it difficult for workers to focus and easily fall asleep. Work accidents that often occur are minor accidents such as first aid kits and medical treatment, but there was a serious accident in 2018 caused by human error.